Strategi Alih Kode Bahasa Maumere dalam Pembelajaran Bahasa Indonesia Akademik di Perguruan Tinggi - Deni Maswar; Nurkhairati Nurkhairati; Natalia Nastuti; Maria Nona Elvin; Yeremias Bardi (STIKes Ibnu Sina Ajibarang, 2026)
This study investigates code-switching strategies between Indonesian and the Maumere local language in academic Indonesian language learning at the university level. In many higher education contexts, the dominance of standard Indonesian as the sole medium of instruction often creates cognitive, linguistic, and cultural distance for students who come from strong local language backgrounds. This qualitative study aims to describe the forms, pedagogical functions, and academic implications of Maumere–Indonesian code-switching in classroom interaction. Employing a case study design, data were collected through classroom observations, in-depth interviews with lecturers and students, and analysis of learning documents. The findings reveal that code-switching occurs systematically at the opening of lessons, during the explanation of abstract concepts, and in small-group discussions. The Maumere language functions as a cognitive and affective bridge that facilitates comprehension, increases student participation, and strengthens academic literacy. The study concludes that pedagogically controlled code-switching supports additive bilingualism and contributes positively to inclusive, contextual, and culturally responsive academic learning in multilingual higher education settings.